#### Answer

Applying vertical stretching by factor of $2$ and then the translation by $2$ to the right we get
$$y=2\sqrt{7x-10-x^2}.$$

#### Work Step by Step

Fist note that the "width" of the graph remains the same because $3-0=5-2$. This means that there is no horizontal stretching/shrinking, only rightwards translation by $2$. Then note that the maximum of the original function is at $1.5$ while for the new function it is $3$ which is $2$ times bigger so there is vertical stretching by the factor of $2$. Applying these transformations:
$$f(x)\to f(x-2)\to 2f(x-2)$$
so the function from the graph is actually
$$y = 2\sqrt{3(x-2)-(x-2)^2} =\\2\sqrt{3x-6-x^2+4x-4}=2\sqrt{7x-10-x^2}.$$